2014
DOI: 10.3233/bme-140966
|View full text |Cite
|
Sign up to set email alerts
|

Influence of modified alginate hydrogels on mesenchymal stem cells and olfactory bulb-derived glial cells cultures

Abstract: BACKGROUND: Great potential of cellular therapies has generated extensive research in the field of cells harvesting and culturing. Transplantation of cell cultures has been used in a variety of therapeutic programs but in many cases it appeared that biomaterial scaffold or sheath would enhance cells regenerative potential. OBJECTIVE: Hydrogels composed of different proportions sodium and calcium alginates, were undertaken to evaluate their influence on mesenchymal stem cells and olfactory bulb-derived glial ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…Biological experiments were approved by the Local Ethics Committee. Glial cells derived from olfactory bulb were isolated using the modified procedure described earlier [48,55]. Olfactory bulbs dissected from three neonatal pups' brains were placed in Hank's balanced salt solution (HBSS).…”
Section: Cell Isolationmentioning
confidence: 99%
“…Biological experiments were approved by the Local Ethics Committee. Glial cells derived from olfactory bulb were isolated using the modified procedure described earlier [48,55]. Olfactory bulbs dissected from three neonatal pups' brains were placed in Hank's balanced salt solution (HBSS).…”
Section: Cell Isolationmentioning
confidence: 99%
“…1 Regenerative medicine and tissue engineering offer patients both stem-cell-based therapy as well as biomaterial scaffolds, which are crucial for efficient treatment. [2][3][4] However, it has been shown that aging negatively correlates with stem cell multipotency, which might seriously limit their regenerative potential. In parallel with organism aging, progenitor cells lose their self-renewal, metabolic activity, and differentiation potential.…”
Section: Introductionmentioning
confidence: 99%
“…Various cell therapies, such as the use of OSCs, have been tested in the last decade [19,[42][43][44][45][46]. Transplanted olfactory cells promoted tissue nerve regeneration by paracrine signaling and by creating a conductive environment [47]. Although these studies showed partial success, an insufficient cell purification can cause complications by co-transplantation of mucusproducing cells [22,48,49].…”
Section: Discussionmentioning
confidence: 99%